Why Do Shoppers Use Cash? Evidence from Shopping Diary Data - Naoki Wakamori; Angelika Welte (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
Recent studies find that cash remains a dominant payment choice for small-value transactions despite the prevalence of alternative methods of payment such as debit and credit cards. For policy makers an important question is whether consumers truly prefer using cash or merchants restrict card usage. Using unique shopping diary data, we estimate a payment choice model with individual unobserved heterogeneity (demandside factors) while controlling for merchants' acceptance of cards (supply-side factors). Based on a policy simulation where we impose universal card acceptance among merchants, we find that overall cash usage would decrease by only 7.7 percentage points, implying that cash usage in small-value transactions is driven mainly by consumers' preferences.
urn:nbn:de:bvb:19-epub-17347-7
Keywords: G2; D1; C2; 330; Money demand; Payment methods; Consumer financial behavior